Analisis Partikulat di Udara Ambien Kawasan Kota Tua Jakarta - Celine Millennia Palureng; Hernani Yulinawati; Asih Wijayanti (Jurnal Serambi Engineering, 2023)
DKI Jakarta Provincial Government has officially implemented a Low Emission Zone (LEZ) in the Kawasan Kota Tua Jakarta to overcome the problem of air pollution. Kawasan Kota Tua Jakarta is a cultural heritage area that applies LEZ, this study was carried out with several objectives, namely analyzing the concentration of TSP based on Ambient Air Quality Standard (AAQS) and comparing the concentration of TSP inside and outside the LEZ. This study uses descriptive quantitative research methods. Sampling was taken using a portable High Volume Air Sampler (HVAS) and analyzed based on SNI 7119-3:2017. 84 samples were taken at 4 location points for 7 days (morning, afternoon, evening) between March-May 2022. The concentration of TSP still met the AAQS used, namely PP 22/2021 (230µg/Nm3 within 24 hours). The highest average concentration is at point 3 (non-LEZ) is 60µg/Nm3 and the lowest is at point 2 (LEZ) is 33µg/Nm3. The range of TSP concentrations at the LEZ location is 5-73µg/Nm3 and 9-80µg/Nm3 in nonLEZ. The concentration of TSP in the 4 sampling locations still meets the AAQS. TSP concentration at the sampling point locations in the non-LEZ area has a much larger range of values when compared with the sampling point inside LEZ area.